‘Making Connections, Changing Lives’: Imaginaries of Commonality and Difference in Artisanal Weaving Tourism - Kaitlyn Rabach (Janeway JS, 2018)
Prompted by a brief encounter over four years ago in Ifrane, Morocco, this article explores the contradictions involved in the industry of weaving and feminist tourism, a type of travel where tourists, mostly women from Central Europe and North America, visit weaving cooperatives in Latin America, North Africa, and Southeast Asia. Though searching for solidarity and connection, these tourists simultaneously retain enough separation from weavers that they continue to feel both entitled and obligated to ‘help’ the artisans through the power of their purchases. These tourists, then, push forth two narratives: one of commonality and the other of difference. This tension is not isolated within the weaving tourism industry, but is rather situated between a larger framework of uneven global processes and the commoditisation of women’s bodies and development. However, current literature surrounding tourism imaginaries emphasises narratives around difference, often failing to recognise commonality as a motivating factor for tourists to choose certain destinations and types of tours. This case study, using my own experiences on a weaving tour, as well as a discourse analysis of tourists’ pre-tour narratives and post-tour tales, deconstructs some of these contradictory accounts to better understand imaginaries around global solidarity, gender identity, and womanly obligations within touristic encounters.